Analisis tingkat literasi keuangan syari’ah masyarakat usia produktif - Zulfa Hilmi; Dina Patrisia (Jurnal Kajian Manajemen dan Wirausaha, 2020)
This study aims to measure the level of Islamic Financial Literacyand to find out whether there is independentvariable effect, including gender, based on age, the last education and the average incomes per month, on thedependent variable, which is Islamic financial literacy. The dependent variable is measured by fourcomponents, namely financial knowledge, loans, investment and savings, and insurance. In this study, 320respondents were sampled. The data processing is done using SPSS. Based on the results of testing thehypothesis that has been done, it was found that gender, the last education and the average incomes per monthhave a significant effect on the level of islamic financial literacy. While based on age, there is no significanteffect on the level of respondent's Islamic financial literacy in the productive age community in the city ofPadang.